PENGARUH PELATIHAN, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA GOLDEN VIEW HOTEL BATAM - Indriana, Rika; Heryenzus, Heryenzus (LPPM Universitas Putera Batam, 2021)
The inspection is carried out at a hotel in Batam, for example Golden View Hotel Batam. This study examines the impact of training, benefits, and discipline on hotel performance. The survey was conducted for all hotel staff with a total of 120 respondents. Linear multivariate analysis was used to continue the SPSS 25 software. Reflecting on the test results, could seen by that training result there is a positive or good and significant effect for staff performance, compensation have a positive or good effect for employee benefits, also workplace is effective and important to the performance of employees. The test results simultaneously obtained that the Fcount value is 74.588 and the Ftable value is 2.683. According to the t-test standards, H0 rejected and Yes passed, which means that training (X1), compensation (X2) and work discipline (X3) are related to employee performance (Y), which is what changes training (X1).), salary (X2) affects and disciplinary activities (X3) show effective and important for employee efficiency (Y).